Islamic Financial Development, Economic Growth and CO2 Emissions in Indonesia - Azwar Iskandar; Bayu Taufiq Possumah; Khaerul Aqbar (Bank Indonesia, 2020)
This study aims to investigate the dynamic relationship between Islamic financial development, economic growth, and CO2 emissions with Environmental Kuznets Curve (EKC) approach in Indonesia over the 2000-2018 period. This study employs the Auto Regressive Distributed Lag (ARDL) bound testing approach and the Error Correction Mechanism (ECM) to examine the existence of long-run and short-run relationship between variables. From the results of the model, we do not find any support for the existence of the EKC for Indonesia. Moreover, the results present that there is no dynamic relationship in the short run among growth, Islamic finance development and CO2 emission. Long-run findings suggest that CO2 emission from transport; other sectors, excluding residential buildings and commercial and public services; and residential buildings and commercial and public services sector are significantly associated to the Islamic finance development in Indonesia. The findings of this study shows that Islamic finance development can help the country to adjust its CO2 emissions and play its role in protecting the environment by encouraging environmental-friendly and energy-efficient projects. A strong and efficient financial sector would be helpful in facilitating the investment process by advancing loans for business in condition with curbing CO2 emissions.